Modeling of habitat suitability for sea cucumber ranching in Sintok Island, Karimunjawa National Park, Indonesia. Issue 1 (December 2021) - Hartati, R; Alya, T S; Zainuri, M; Ambariyanto, A; Widianingsih, W; Ario, R; Pratikto, I; Sulisyati, R
Abstract: Increasing demand for marine resources, such as sea cucumber, has led to widespread interest in their conservation, one of which is sea ranching. This study sought to identify habitat suitability for sea cucumber Holothuria scabra ranching. The proposed location was Sintok Island, one small island part of Karimunjawa Archipelagos. The HSI (Habitat Suitability Index) model was used to identify potential sites for sea cucumber ranching. Twelve habitat factors were used as input variables for the HSI model: sediment classification, water temperature, salinity, pH, dissolved oxygen, depth, transparency, current, depth, organic matter and chlorophyll-a of the sediment, seagrass density, and tide. The weighting of each habitat factor was defined through the Delphi method. Sediment classification and seagrass density were the most and less important condition affecting the HSI of H. scabra in the different study areas with weighing index of 0.2191 and 0.015 respectively. The HSI of Southern Station (Station 1) was relatively low (0.79-0.81), meaning the site was not suitable for sea ranching of H. scabra . In contrast, the western (Station 2) and the northern part (Station 3) of Sintok Island, were preferable sites, suitable as habitats for restoration efforts in sea ranching.